Pengembangan sistem informasi laboratorium pendidikan Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Yogyakarta - Wahyu Widyantoro; Sarifah Sya'diyah; Ana Kurniawati Fathonah (Health Educational Laboratory, 2024)
Educational laboratories are a very important supporting facility for the continuity of education in Vocational Higher Education. School laboratory management activities in the Environmental Health Department of the Yogyakarta Ministry of Health Polytechnic are all forms of recording items and activities that occur in the laboratory. Considering the importance of laboratory functions, good laboratory management is an absolute necessity. This allows schools to more easily obtain real data on the condition of goods and activities in the laboratory. The aim of this research is to help make things easier for laboratory managers, especially inventory data, equipment conditions, borrowing and returning equipment, laboratory schedules, laboratory rules and monitoring records of laboratory use activities. The method used is ADDIE (Analysis, Design, Development & Implementation and Evaluation), starting from preliminary studies, system creation and system testing to produce a web-based laboratory management information system, because compared to paper-based, laboratory management activities use a web-based information system. The web is considered more efficient to implement, because with the web all forms of recording can be easily done and if data is needed, all authorized parties can easily obtain the data. It is hoped that the use of a website-based laboratory information system will help optimize management in monitoring laboratory activities, borrowing equipment, using materials and laboratory data.